Rietveld refinement of cassiterite: A caveat for meticulous sample preparation - Klementova,M.; Rieder,M.; Weiss,Z. (Journal of the Czech Geological Society, 2000)
Powder mounts used to collect diffraction data for Rietveld refinements should be prepared with utmost care and maximum skill. Variables modelling preferred orientation may be included in the refinement only if the material is prone to it and if the techniques used in preparing the mount could have allowed or accentuated its presence.
Keywords: Rietveld refinement; cassiterite; preferred orientation